€1 billion for EU Water Fund - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2003)
The European Commission has recently proposed the establishment of a European Union Water Fund, with a budget of ?1 billion, to help give people in the 77 African, Caribbean and Pacific (ACP) signatory countries to the Cotonou Partnership Agreement acce